PERUMUSAN STRATEGI ORGANISASI TERHADAP MUTU PENDIDIKAN PADA DINAS PENDIDIKAN KABUPATEN SIDENRENG RAPPANG - Kardina Herman (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2017)
This study aims to determine the effect of Organizational Strategy Formulation Of Quality Education at the District Education Office Sidrap and the factors that affect Formulation Strategies Against Organization Quality of Education at the Department of Education Sidenreng Rappang. The data collection techniques using observation, questionnaires, research literature, interviews. The number of population in this study as many as 60 people using the total sample with the number of 60 people, data processing techniques using frequency tables with Likert scale. The results of this study indicate that Formulation Strategies Against Organization Quality of Education at the District Education Office Sidrap obtained a score of 71% is included in both categories. Factors affecting Strategy Formulation Against Organization Quality of Education at the Department of Education Sidenreng Rappang that vision factors obtained a score of 70.75% categorized as good, mission factors obtained a score of 74.75% categorized as good and 74% target factor considered good.